Research on unhealthy food and beverages advertising targeting children: Systematic literature review and directions for future research. Issue 4 (November 2022) - Srivastava, Ritu; Gupta, Parul
The rising level of childhood obesity across the globe has escalated the worries of World Health Organization (WHO), health practitioners, policymakers, and regulators. One of the most prominent factors that promote unhealthy eating habits of children is the heavy advertising of food and beverages (F&B) targeted at children. This has deepened the concerns of stakeholders about the persuasion ethics of firms aggressively promoting unhealthy foodstuff to young consumers. This article presents a systematic literature review of scholarly research on the advertising of unhealthy F&B targeted at children. A systematic review of 70 peer-reviewed articles is conducted through the theoretical lens to present their contributions. Synthesising the findings of empirical studies, the scholarly research is classified into six core research themes. We elaborate on directions for future research: Theory, Context, and Methods and distil specific research questions for future studies.